The Role of Small United Nations Member States - Christensen, Hanne (Advances in Social Sciences Research Journal, 2024)
This article outlines the situation of small member states of the United Nations which make up the majority of the membership. It shows that smallness is far from insignificance. Small UN members are active, diligent, and necessary partners for significant member states in the endeavor to get resolutions through in the General Assembly. They work in close collaboration with and assist one another, share insightful knowledge and through networking can cover the entire field of activities of the United Nations. Yet being short staffed, getting through valuable information of a heavy-written nature issued by the UN to do their job presents a challenge.